Uriel Weinreich’s “Languages in Contact” in the Soviet Union: Treading a Dangerous Ground - Litvinyak, Oleksandra (Respectus Philologicus, 2021)
In a democratic society with a market economy, editorial policy is often a matter of financial feasibility rather than anything else. Meanwhile, totalitarian societies approach it from a different angle, frequently putting political considerations in the centre. Living behind the Iron Curtain, Soviet scholars had very limited access to Western publications – very few of them were translated into the languages of Soviet republics. What is more, research shows that they were subject to censorship, just like literary works. Besides, the work of a translator, being invisible to the majority of readers, could be quite dangerous and ruin one’s scholarly career. Thus, a scholar embarking on a translation journey to acquaint their colleagues with the best samples of world research had to be very considerate. Such was the case of the Russian translation of Uriel Weinreich’s seminal book Languages in Contact done by the Ukrainian linguist, translator, lexicographer, and educator Yuriy Zhluktenko. The present paper explores the matter of censorship and self-censorship in this translation and its paratexts.